2008
DOI: 10.1534/genetics.108.089680
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Heterosis for Yield and Yield Components in Rapeseed (Brassica napus L.) by Quantitative Trait Locus Mapping

Abstract: The main objective in this research was the genetic analysis of heterosis in rapeseed at the QTL level. A linkage map comprising 235 SSR and 144 AFLP markers covering 2045 cM was constructed in a doubledhaploid population from a cross between the cultivar ''Express'' and the resynthesized line ''R53.'' In field experiments at four locations in Germany 250 doubled-haploid (DH) lines and their corresponding testcrosses with Express were evaluated for grain yield and three yield components. The heterosis ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
199
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(234 citation statements)
references
References 32 publications
28
199
2
3
Order By: Relevance
“…We also confirmed that PrBn is still the major determinant for this trait at the species level. Interestingly Radoev et al (2008) recently mapped a QTL that colocalizes with PrBn and is involved in determining the number of seeds per silique in a cultivar 3 resynthesized segregating population. As the number of seeds per silique is directly related to meiotic regularity, which is different between natural and resynthesized B. napus (for review, see Nicolas et al, 2008), this result could indicate a broader role for PrBn in regulating the diploid-like meiotic behavior of B. napus.…”
Section: Discussionmentioning
confidence: 99%
“…We also confirmed that PrBn is still the major determinant for this trait at the species level. Interestingly Radoev et al (2008) recently mapped a QTL that colocalizes with PrBn and is involved in determining the number of seeds per silique in a cultivar 3 resynthesized segregating population. As the number of seeds per silique is directly related to meiotic regularity, which is different between natural and resynthesized B. napus (for review, see Nicolas et al, 2008), this result could indicate a broader role for PrBn in regulating the diploid-like meiotic behavior of B. napus.…”
Section: Discussionmentioning
confidence: 99%
“…QTLs for seed yield and yield-related traits in B. napus were collected from 15 articles published over the last 20 years (Butruille et al 1999;Quijada et al 2006;Udall et al 2006;Zhao et al 2005;Chen et al 2007;Shi et al 2009;Fan et al 2010;Wang and Guan 2010;Radoev et al 2008;Basunanda et al 2010;Shi et al 2011;Zhang et al 2011;WĂŒrschum et al 2012;Zhang et al 2012;Yang et al 2012b). The collected information included traits, species, QTL-linked markers, name of the main QTL, linkage group, logarithm of odds (LOD) value, confidence interval, proportion of the phenotypic variation explained by the QTL, additive effect, dominance effect, peak position, reference, first author, and published time (as shown in Supplementary Table 1).…”
Section: Collection Of Qtls For Seed Yield and Yield-related Traits Imentioning
confidence: 99%
“…However, these hypotheses are largely conceptual and do not explain the molecular basis of heterosis (Hochholdinger and Hoecker, 2007;He et al, 2011). Recently, genetic quantitative trait locus and high-throughput transcript profiling have been used to analyze the heterotic phenotypes and indicate that a large number of genes may be associated with heterosis in all possible modes of action (Frascaroli et al, 2007;Uzarowska et al, 2007;Radoev et al, 2008;Meyer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%